Prädiktive Lichtfunktionen für volladaptive Scheinwerfersysteme - Omerbegovic, Said (Spektrum der Lichttechnik / Karlsruher Institut für Technologie (KIT), Lichttechnisches Institut, 2019)
In this work, the realisation of an adaptive driving beam is examined that is based on the motion prediction of the ego vehicle and other traffic participants. Furthermore, light functions are developed and analysed regarding their effectiveness that project situation adaptive recommendations for action in front of the vehicle regarding a turn or lane change intention of the driver.